Implementation of a PMTCT programme in a high HIV prevalence setting in Johannesburg, South Africa: 2002-2015 - Coceka Mnyani; Carol L. Tait; Remco P.H. Peters; Helen Struthers; Avy Violari; Glenda Gray; Eckhart J. Buchmann; Matthew F. Chersich; James A. McIntyre (AOSIS, 2020)
Background: Great strides have been made in decreasing paediatric human immunodeficiency virus (HIV) infections, especially in sub-Saharan Africa. In South Africa, new paediatric HIV infections decreased by 84% between 2009 and 2015. This achievement is a result of a strong political will and the rapid evolution of the country's prevention of mother-to-child transmission (PMTCT) guidelines. Objectives: In this paper we report on the implementation of a large PMTCT programme in Soweto, South Africa. Methods: We reviewed routinely collected PMTCT data from 13 healthcare facilities, for the period 2002-2015. Antiretroviral therapy (ART) coverage among pregnant women living with HIV (PWLHIV) and the mother-to-child transmission (MTCT) rate at early infant diagnosis were evaluated. Results: In total, 360 751 pregnant women attended the facilities during the review period, and the HIV prevalence remained high throughout at around 30%. The proportion of PWLHIV presenting with a known HIV status increased from 14.3% in 2009 when the indicator was first collected to 45% in 2015, p 0.001. In 2006, less than 10% of the PWLHIV were initiated on ART, increasing to 88% by 2011. The MTCT rate decreased from 6.9% in 2007 to under 1% from 2013 to 2015, p 0.001. Conclusion: The achievements in decreasing paediatric HIV infections have been hailed as one of the greatest public health achievements of our times. While there are inherent limitations with using routinely collected aggregate data, the Soweto data reflect progress made in the implementation of PMTCT programmes in South Africa. Progress with PMTCT has, however, not been accompanied by a decline in HIV prevalence among pregnant women.